2020
DOI: 10.1002/ehf2.12906
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and prognostic implications of tricuspid regurgitation in patients with arrhythmogenic cardiomyopathy

Abstract: Aims Arrhythmogenic cardiomyopathy (AC) is characterized by right ventricular (RV) dilatation and dysfunction and is often seen in combination with tricuspid regurgitation (TR). The aim of this study was to investigate the characteristics and prognostic implications of TR in patients with AC. Methods and results Clinical, echocardiographic, and cardiac magnetic resonance data of 52 patients with AC fulfilling 2010 Task Force criteria in a single centre were retrospectively evaluated. TR in AC was classified as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Previous studies demonstrated that LVEF reduction, 15 atrial arrhythmias, 31 and presence of moderate to severe TR 32 had an adverse impact on HF progression. In our study, first-degree AVB showed a significant relation with HF outcomes, which was consistent with another study.…”
Section: Prior Studies On Risk Predictionmentioning
confidence: 96%
“…Previous studies demonstrated that LVEF reduction, 15 atrial arrhythmias, 31 and presence of moderate to severe TR 32 had an adverse impact on HF progression. In our study, first-degree AVB showed a significant relation with HF outcomes, which was consistent with another study.…”
Section: Prior Studies On Risk Predictionmentioning
confidence: 96%
“…29 Regarding valvular assessment, tricuspid regurgitation is associated with poor prognosis. 30,31 There are limited data regarding surgical correction of functional tricuspid regurgitation in patients with ARVC; however, a case series of 3 patients suggested it could have a therapeutic role in selected patients. 32 In addition to decreased RV-FAC, as identified by the 2010 Task Force Criteria, 2 other indices of right ventricular dysfunction have been reported.…”
Section: Echocardiographymentioning
confidence: 99%
“…Tricuspid regurgitation (TR) is a poor and independent prognostic factor for the general population and patients with various cardiac diseases. 1 , 2 , 3 , 4 , 5 With aging, the prevalence of moderate or severe TR is increasing as isolated TR with atrial fibrillation increases. 5 , 6 , 7 Clinical presentation often demonstrates a long course and can be controlled temporarily with diuretics.…”
mentioning
confidence: 99%